2011
DOI: 10.1093/ndt/gfq750
|View full text |Cite
|
Sign up to set email alerts
|

Spironolactone inhibits hyperglycemia-induced podocyte injury by attenuating ROS production

Abstract: We conclude that hyperglycemia in diabetes, independent of plasma aldosterone concentration, induces podocyte injury through MR-mediated ROS production and leads to proteinuria. SPL inhibits hyperglycemia-induced podocyte injury by attenuating ROS production.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
53
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(62 citation statements)
references
References 57 publications
6
53
0
3
Order By: Relevance
“…The gene expression levels of 8-OHdG and Nox4 in the kidney of db/db mice were relatively low at 6 weeks of age, but their expression markedly increased with increasing albuminuria and mesangial expansion at 9 weeks of age. Consistent with previous studies [25,26,27], these results indicate that oxidative stress is involved in the pathogenesis of diabetic nephropathy. Telmisartan suppressed albuminuria and mesangial expansion in db/db mice without affecting blood glucose levels or blood pressure.…”
Section: Discussionsupporting
confidence: 93%
“…The gene expression levels of 8-OHdG and Nox4 in the kidney of db/db mice were relatively low at 6 weeks of age, but their expression markedly increased with increasing albuminuria and mesangial expansion at 9 weeks of age. Consistent with previous studies [25,26,27], these results indicate that oxidative stress is involved in the pathogenesis of diabetic nephropathy. Telmisartan suppressed albuminuria and mesangial expansion in db/db mice without affecting blood glucose levels or blood pressure.…”
Section: Discussionsupporting
confidence: 93%
“…H 2 O 2 (500 μM) treatment also increased HO-1 protein levels. Several similar studies have been described in other cell types [50,51,52]. However, several possible mechanisms most likely exist for HG-induced ROS generation, which mediated the up-regulation of HO-1 expression.…”
Section: Discussionsupporting
confidence: 56%
“…Further clinical and experimental studies have demonstrated an increased level of inflammatory markers such as macrophage-chemoattractant protein 1 and transforming growth factor b1, osteopontin, interleukin 1 (IL1), and IL6 expression due to aldosterone excess (14,15,16,17,18). Especially, the excess of aldosterone in combination with an elevated salt intake results in renal inflammation, fibrosis, podocyte injury, and mesangial cell proliferation (19,20).…”
Section: Introductionmentioning
confidence: 99%